2009
DOI: 10.1557/jmr.2009.0315
|View full text |Cite
|
Sign up to set email alerts
|

Formation mechanism of Sn-patch between SnAgCu solder and Ti/Ni(V)/Cu under bump metallization

Abstract: An Sn-patch formed in Ni(V)-based under bump metallization during reflow and aging. To elucidate the evolution of the Sn-patch, the detailed compositions and microstructure in Sn–Ag–Cu and Ti/Ni(V)/Cu joints were analyzed by a field emission electron probe microanalyzer (EPMA) and transmission electron microscope (TEM), respectively. There existed a concentration redistribution in the Sn-patch, and its microstructure also varied with aging. The Sn-patch consisted of crystalline Ni and an amorphous Sn-rich phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…1 of Ref. 16. In the following, conventional TEM, STEM, and HRTEM characterization of the consumed Ni(V) and porous structure microstructures are presented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 of Ref. 16. In the following, conventional TEM, STEM, and HRTEM characterization of the consumed Ni(V) and porous structure microstructures are presented.…”
Section: Resultsmentioning
confidence: 99%
“…The observation that V was immobile and Ni diffused out from Ni-V alloys has been reported in the literature. [9][10][11][12][13][15][16][17][18][19][20][21] …”
Section: Stem Line Scan Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sn-patch was observed in the Ni(V) layer after reflow, in agreement with the literature report. [8][9][10][11][12][13] The area ratio of Sn-patch to the Ni(V) layer was around 13.2% in the Sn-Ag-Cu/UBM 05 solder joint after reflow, and increased to 14.1% after aging for 1000 h due to interdiffusion of Ni and Sn (Fig. 3b).…”
Section: Methodsmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13] Recently, it was revealed that the Sn-patch consists of an amorphous Sn phase and crystalline V 2 Sn 3 , and a mechanism for its formation was proposed. 11 However, there is little literature concerning the relationship between Sn-patch and solder joint reliability. Zheng et al 12 reported that the fracture surface of Sn-3.5Ag-1.0Cu solder joints with Ti/Ni(V)/Cu UBM became brittle after 30 reflows.…”
Section: Introductionmentioning
confidence: 99%